2001
DOI: 10.1007/s11738-001-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abscisic acid on endogenous IAA, auxin protector levels and peroxidase activity during adventitious root initiation in Vigna radiata cuttings

Abstract: Endogenous levels of free and conjugated IAA, auxin protectors (Prs) and peroxidase (PER) activity and their relation to adventitious root initiation (ARI) were investigated at the potential sites of adventitious rooting in relation to exogenous application of 250 plVl ABA during the first 120 h after treatment.Cuttings from 7-day-old mung bean [Vigna radiata (L.) Wilcz.] seedlings were treated with 125, 250, and 500 pM ABA for 24 h. ABA significantly stinmlated ARI but extremely inhibited epicotyl growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…ABA is required for ARF, but high ABA levels inhibit this process [ 26 , 31 ]. Tartoura [ 46 ] applied exogenous ABA to Vigna radiata cuttings during the initiation of ARF and found that the IAA peak was delayed and the length of rooting induction was extended. In our study, the ABA level was always low in the cambium of rejuvenated soft shoots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ABA is required for ARF, but high ABA levels inhibit this process [ 26 , 31 ]. Tartoura [ 46 ] applied exogenous ABA to Vigna radiata cuttings during the initiation of ARF and found that the IAA peak was delayed and the length of rooting induction was extended. In our study, the ABA level was always low in the cambium of rejuvenated soft shoots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1), which may explain the difference in number of adventitious roots between the two experiments. ABA is also inhibited by fluridone, however, it is unlikely that the increase in rooting is due to reduced ABA because ABA has been shown to promote adventitious rooting in Vigna radiate and Hedera helix 19,20 and has no effect in Arabidopsis (data not shown). These results demonstrate that fluridone could be used to induce adventitious rooting in stem cuttings of pea.…”
Section: Inhibiting Strigolactone Promotes Adventitious Rooting In Peamentioning
confidence: 99%
“…T h e r e is substantial evidence that auxins play a crucial role in adventitious root formation (Caboni et al 1997, Tartoura 2001), but little is known about their specific action and their interactions with other compounds . Several studies describing changes of peroxidase (POX) and polyphenoloxidase (PPO) activities in relation to the rooting process in cuttings were published (Gonzalez et al 1991.…”
Section: Introductionmentioning
confidence: 99%